Perkembangan penelitian aplikasi rumput laut sebagai bahan pangan di Indonesia: tinjauan literatur - Amin Pamungkas; Bakti Berlyanto Sedayu; Arif Rahman Hakim; Putri Wullandari; Ahmat Fauzi; Toni Dwi Novianto (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Seaweed contains high dietary fiber and low fat, which is beneficial for health. The content of omega-3 and its antioxidants supports public awareness of a healthy lifestyle. This review paper aims to investigate the research progress of seaweed as food in Indonesia. The research progress in this study focus on seaweed addition to food and its effect on the chemical and organoleptic characteristics. Seaweed research as food has been developed. As one of the seaweed producers, Indonesia needs to increase seaweed use to increase seaweed value and provide sustainable, nutritious food. Food that can combine with seaweed is dodol, jelly candy, fish sticks, pempek, tempeh, and fish balls. The addition of seaweed to food increases protein, water, iodine, and fiber. Seaweed fiber content can decrease cholesterol levels and help regulate blood glucose levels which can prevent cardiovascular disease. Aroma and flavor are sensory properties strongly affected by seaweed in food. The seaweed addition has to consider the sensory properties that determine consumer acceptance. The suitable composition of seaweed addition to food can improve nutrition and consumer acceptance